Development of a Desmocollin-3 Active Mouse Model Recapitulating Human Atypical Pemphigus - Lotti, Roberta; Atene, Claudio Giacinto; Marconi, Alessandra; Di Rocco, Giulia; Reggiani Bonetti, L.; Zanocco Marani, Tommaso; Pincelli, Carlo (Frontiers in Immunology, 2019)
Pemphigus vulgaris (PV) is a life-threatening mucocutaneous autoimmune blistering disease. It is often associated with autoantibodies to the desmosomal adhesion proteins Desmoglein 3 (DSG3) and Desmoglein 1 (DSG1). Recently, auto-antigens, such as desmocollins and others have been described in PV and in atypical pemphigus forms such as Pemphigus Herpetiformis (PH), Pemphigus Vegetans (PVeg) and Paraneoplastic Pemphigus (PP). Desmocollins belong to a cadherin subfamily that provides structure to the desmosomes and plays an important role in cell-to-cell adhesion. In order to verify the pathogenic activity of anti-Desmocollin 3 (DSC3) antibodies, we developed an active disease model of pemphigus expressing anti-DSC3 autoantibodies or anti-DSC3 and anti-DSG3 antibodies. This approach included the adoptive transfer of DSC3 and/or DSG3 lymphocytes to Rag2-/- immunodeficient mice that express DSC3 and DSG3. Our results show that the presence of anti-DSC3 auto-antibodies is sufficient to determine the appearance of a pathological phenotype relatable to pemphigus, but with features not completely super-imposable to those observed in the DSG3 active model, suggesting that the DSC3 active model might mimic the atypical pemphigus. Moreover, the presence of both anti-DSC3 and anti-DSG3 antibodies determines a more severe phenotype and a slower response to prednisolone. In conclusion, we have developed an adult DSC3 pemphigus mouse model that differs from the DSG3 model and supports the concept that antigens other than desmogleins may be responsible for different phenotypes in human pemphigus.